Die theologische Fakultät Innsbruck zwischen "Anschluß" und Aufhebung (1938) - Batlogg, Andreas R. (Zeitschrift für katholische Theologie, 1998)
The Theology Faculty of the University of Innsbruck was closed down by the Nazis on 22 July 1938. The closure was the final act in a long succession of chicanery that had begun on March 12, the day of the so-called Anschluβ (attachement) of Austria to the German Reich. The "Diarium Facultatis Theologiae 1857-1957", which records these events, has never been edited. The above reproduces the text in full for the period between September 1937 and August 1938, covering the Anschluβ, the Winter Semester 1937-38, and the closure of the Faculty. There are also two supplementary texts, written by Deans of the Faculty (J. A. Jungmann and E. Coreth) during the 1950s. The edited material comprises only nine of the 339 pages from the whole text, but these pages mark undoubtedly the saddest chapter of the first 100 years of the Faculty.